ChemInform Abstract: Fluorine‐Rich Fluorides: New Insights into the Chemistry of Polyfluoride Anions. Issue 37 (September 2015) - Vent‐Schmidt, Thomas; Brosi, Felix; Metzger, Jens; Schloeder, Tobias; Wang, Xuefeng; Andrews, Lester; Mueller, Carsten; Beckers, Helmut; Riedel, Sebastian
Abstract The Cs+[F3]‐ ion pair as well as a so far unknown higher polyfluoride anion, [F5]‐ are matrix‐isolated by reaction of laser‐ablated Cs atoms with F2 in excess neon at 4 K, and characterized by IR spectroscopy and coupled‐cluster molecular structure calculations.